A Micromechanical Cantilever‐Based Liposome Biosensor for Characterization of Protein‐Membrane Interaction. Issue 3 (23rd September 2015) - Zhang, Z.; Sohgawa, M.; Yamashita, K.; Noda, M.
Abstract: We have newly evaluated the interaction of lipid membrane with two different proteins of lysozyme and carbonic anhydrase from bovine (CAB) using a micro cantilever‐based liposome biosensor with a new droplet‐sealing structure. Herein 1, 2‐dipalmitoyl‐sn‐glycero‐3‐phosphocholine (DPPC) liposomes are used as model lipid membrane and are immobilized on the surface of cantilever. The interaction of DPPC liposome with the target protein causes deflection of the micro‐cantilever, which can stably be detected by measuring the resistance change of the strain gauge. The resistance change dependent on time is used to evaluate the characteristic of liposome‐protein interaction. The resistance of the cantilever‐based biosensor increases monotonously with time in both of the two protein solutions. Especially, chronological resistance change depends markedly on both the concentration and species of target proteins. Finally, these results lead us to conclude that the cantilever‐based liposome biosensor with the droplet‐sealing structure facilitates the characterization of protein‐membrane interaction. It also means that this biosensor is a promising candidate device for label‐free detection of concentration and species of different target proteins. Abstract :